FARMERS' PERSPECTIVES ON THE ROLE OF SPECIAL EFFORT PROGRAM EXTENDERS (UPSUS) IN NORTH TIMOR DISTRICT - Falo, Marsianus (International Journal of Scientific Research and Management (IJSRM), 2022)
One of the districts participating in the Special Efforts (Upsus) program for Rice, Corn and Soybeans (Pajale) in East Nusa Tenggara (NTT) is North Central Timor (TTU) district, especially in Insana sub-district. In order to realize the optimal management of the implementation of the Upsus program, it is necessary for the participation of extension workers in facilitating farmers to increase their knowledge, attitudes and skills in terms of farmer capacity. This study aims to explore the farmer's perspective on the role of extension workers as educators, facilitators, consultants, dynamists, motivators, organizers, and evaluators as well as the factors that influence the implementation of the role of extension workers in facilitating the management of the Upsus Program implementation in TTU District. This study uses a descriptive method with a qualitative approach. The data were analyzed descriptively qualitatively, namely the data obtained were tabulated and then processed with qualitative analysis, namely the technique of examining data derived from the views that were in the minds of the people (informants) which included three streams of activities simultaneously, namely data reduction (data reduction), data presentation (data reduction), and data presentation (data reduction). display), and drawing conclusions (conclusion drawing/verivication), which is supported by the Nvivo 12 analysis tool. The research location was chosen purposively (deliberately) that was determined by researchers in Insana District because it has a Farmer Group that has been carrying out Upsus activities for corn plants since 2015. The results showed that the farmers' perspective on the role of extension workers focused on technical assistance in corn cultivation and growing farmer groups as educators, facilitators, consultants, and dynamists in the medium category, while motivators, organizers, and as evaluators were in the low category. The factors identified that influence the activity of the role of the extension worker in TTU District are: the competence of the extension worker to carry out the duties and functions of the extension, the motivation of the extension worker and the orientation of the extension institution.